The effects of frailty, mental health, and cardiac function on quality of life in patients undergoing transcatheter aortic valve replacement - Jinyao Wang; Jun Cui; Xuemei Yang; Shuangyan Tu; Ying Wang; Yan Jiang; Lihong Zhao; Mao Chen; Zhonglan Chen; Yun Bao (Scientific Reports)
Abstract Understanding changes in the quality of life (QoL) and its risk factors can facilitate identify individuals who may benefit from transcatheter aortic valve replacement (TAVR). However, the relationships between frailty, mental health, cardiac function, and QoL in patients after TAVR have not been well-studied. From February 2022 to November 2023, 396 patients who underwent TAVR were selected as a convenience sample. A structural equation model was used to validate the hypothesized model. We employed descriptive statistics, Spearman correlation coefficients, independent-sample t-test, and one-way ANOVA analysis to determine direct correlations. Bootstrapping analysis was used to evaluate the indirect effects. In patients who underwent TAVR, QoL was negatively correlated with NYHA class and frailty phenotype. Specifically, frailty had a statistically direct impact on patients’ mental health (β = 0.237, 95% CI 0.068 to 0.365, p < 0.01) and QoL (β=−0.375, 95% CI −0.524 to 0.193, p < 0.01). Also, patients’ mental health (β = 0.159, 95% CI 0.031 to 0.30, p < 0.05) and cardiac function (β=−0.356, 95% CI −0.599 to −0.168, p < 0.01) showed significant direct effects on QoL. Meanwhile, patients’ mental health played a mediating role in the relationship between frailty and QoL (β = 0.038, 95% CI 0.006 to 0.072, p < 0.05) in patients after TAVR. Future initiatives to raise patients’ awareness of frailty before and after TAVR, especially by considering the possible impact of mental health other than just anxiety and depression, may improve the overall QoL after TAVR. More extensive prospective trials, including psychological interventions tailored to patients after TAVR, are required.